Development of My Social Safe Place (My Solace) website to prevent cyberbullying at SMA Negeri 1 Sidoarjo - Devina Safira Prastowo; A. Rosyid Al Atok; Nur Wahyu Rochmadi (Inovasi Kurikulum, 2025)
Cyberbullying has become a new phenomenon whose existence is quite worrying for the Indonesian nation as a result of the development of science and technology. This study aims to produce website-based learning media to prevent cyberbullying in SMA Negeri 1 Sidoarjo. Based on this objective, the research focuses on the feasibility of the website-based learning media My Social Safe Place (My Solace) through expert validation and assessment of students' pre-test and post-test results using the website. The type of research used is research and development based on adapting the steps developed by Borg and Gall to the research and development flow. Data collection techniques are based on material and media experts' validation results, student and teacher response questionnaires, and pre-test and post-test results. Data analysis uses descriptive analysis, where the quantitative data is analyzed qualitatively. The level of practicality of the My Solace website in small group trials achieved significant changes from the pretest results. The results of the data analysis concluded that the development of the My Solace website to prevent cyberbullying in SMA Negeri 1 Sidoarjo was declared feasible, practical, and effective, so that it can be used as a medium for learning.   Abstrak Perundungan siber menjadi fenomena baru yang keberadaannya cukup mengkhawatirkan bagi bangsa Indonesia sebagai dampak dari perkembangan IPTEK. Penelitian ini bertujuan menghasilkan media pembelajaran berbasis website sebagai salah satu upaya untuk mencegah perundungan siber di SMA Negeri 1 Sidoarjo. Berdasarkan tujuan tersebut maka fokus penelitian terarah pada kelayakan media pembelajaran berbasis website My Social Safe Place (My Solace) melalui validasi para ahli dan penilaian hasil pre-test dan post-test peserta didik dalam penggunaan website. Jenis penelitian yang digunakan ialah penelitian dan pengembangan berdasarkan adaptasi langkah-langkah yang dikembangkan Borg dan Gall disesuaikan dengan alur penelitian pengembangan. Teknik pengumpulan data berdasarkan hasil validasi ahli materi dan ahli media, angket respon peserta didik dan guru serta hasil pre-test dan post-test. Analisis data menggunakan analisis deskriptif dimana data kuantitatif yang diperoleh dianalisis secara kualitatif. Tingkat kepraktisan website My Solace pada uji coba kelompok kecil mencapai perubahan signifikan dari hasil pretest. Hasil analisis data menyimpulkan bahwa pengembangan website My Solace untuk mencegah perundungan siber di SMA Negeri 1 Sidoarjo dinyatakan layak, praktis dan efektif sehingga dapat digunakan sebagai media dalam pembelajaran. Kata Kunci: My Social Safe Place; My Solace; perundungan siber; pengembangan website